الابداع التكنولوجي والقدرة التنافسية في المؤسسة الاقتصادية العمومية في الجزائر حالة الجيل الثالث G3 في فروع سوناطراك بوهران - بوداود, أمينة (Recherches économiques et managériales, 2020)
في بيئة متغيرة غير مستقره متميزة بالتطور السريع لتكنولوجيا المعلومات والاتصالات ، وضعت قواعد جديدة للمنافسة و اضحت القدرة التنافسية هدف بلا منازع لأية شركة تبحث علي ضمان استمراريتها وبقائها . (Chanal&Mothe, 2005) في هذا السياق، Porter (1935) يؤكد أن الابداع هو مفتاح القدرة التنافسية لأنه يؤثر على قدرتها على الحفاظ على المزايا التنافسية المستدامة في الأسواق الناشئة. تقدم هذه المقالة دراسة حول أثر الابداع التكنولوجي في مجال تكنولوجيا المعلومات والاتصالات على القدرة التنافسية للشركة العمومية الاقتصادية في الجزائر من خلال دراسة حالة " الجيل الثالث  "في فروع سوناطراك بوهران. في البداية نقدم مشكلة البحث، الإطار النظري والفرضيات المستمدة منها، ثم نقدم نموذج الدراسة المستخدم وأخيرا سوف نناقش نتائج الانحدار التي تم الحصول عليها. الكلمات المفتاحية: الابداع التكنولوجي،تكنولوجيا المعلومات والاتصالات،القدرة التنافسية   Abstract : In a changing and uncertain environment, characterized by the rapid development of information technology and communication (ie ITC), new competitive rules are established and competitiveness is an undisputed goal for any business looking to ensure its continuity and survival (Chanal&Mothe, 2005). In this context, Porter (1935) emphasizes that innovation is the key to business competitiveness because it affects their ability to maintain sustainable competitive advantages in evolving markets. This article presents a study that examines the impact of technological innovation in the field of information technology and communication (ITC) on the competitiveness of the economic public company in Algeria through the case of " 3G "at the subsidiary Sonatrach Oran. We begin by presenting the research problem, the theoretical framework and hypotheses derived from it, then we develop the analytical model used and finally we will discuss the regression results obtained.   Mots-clés: Technological Innovation, ITC, Competitiveness.